2005
DOI: 10.1111/j.1572-0241.2005.41060.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac, Neuroadrenergic, and Portal Hemodynamic Effects of Prolonged Aldosterone Blockade in Postviral Child A Cirrhosis

Abstract: These data provide evidence that aldosterone blockade by long-term K-Canrenoate administration improves hepatic hemodynamics by lowering HVPG and ameliorates cardiac structure and function by favoring a reduction in LVWT and LVEDV as well. They also show, however, that this therapeutic intervention neither improves left ventricular diastolic dysfunction nor exerts sympathoinhibitory effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
7

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 32 publications
1
32
0
7
Order By: Relevance
“…Recently Pozzi et al [28] confirmed these findings in a human study highlighting a potential protective role of chronic aldosterone blockade currently employed in decompensated cirrhosis. Nevertheless, autoptic findings notably are biased by the nature of the events that lead to death cirrhotic subjects: circumstances like sepsis, shock and hepatorenal syndrome may have a severe impact on cardiac function [22] besides post-mortem heart tissue changes.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Recently Pozzi et al [28] confirmed these findings in a human study highlighting a potential protective role of chronic aldosterone blockade currently employed in decompensated cirrhosis. Nevertheless, autoptic findings notably are biased by the nature of the events that lead to death cirrhotic subjects: circumstances like sepsis, shock and hepatorenal syndrome may have a severe impact on cardiac function [22] besides post-mortem heart tissue changes.…”
Section: Discussionsupporting
confidence: 73%
“…Previous studies have identified structural change of the heart in cirrhotic subjects and postulated its role as the anatomic background of impaired transmitral flow [14,28]. Nevertheless in vivo studies of myocardial tissue characterization in compensated cirrhosis are substantially lacking so far.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pozzi and colleagues [94] recently demonstrated that the use of an aldosterone antagonist, k-canrenoate, for 6 months can reduce the parietal wall thickness of the left ventricle even in patients at an early stage of cirrhosis, the so-called preascitic cirrhosis. The rationale for using an aldosterone antagonist was to counteract the fibrotic effects of aldosterone and reduce the circulatory volume load, and this has the potential of reducing myocardial hypertrophy and stiffness, thereby improving diastolic dysfunction in cirrhosis.…”
Section: Treatment Of Cirrhotic Cardiomyopathymentioning
confidence: 99%